A history of modern Latin America 1800 to the present - Meade,Teresa A. 1948- (Concise history of the modern world, 2016)
A History of Modern Latin America offers a comprehensive and accessible introduction to the rich cultural and political history of this vibrant region from the onset of independence to the present day. Includes coverage of the recent opening of diplomatic relations between the U.S. and Cuba as well as a new chapter exploring economic growth and environmental sustainability ; balances accounts of the lives of prominent figures with those of ordinary people from a diverse array of social, racial, and ethnic backgrounds... --Provided by the publisher.